Puritan iconoclasm during the English Civil War - Spraggon, Julie, 1962- (Studies in modern British religious history ;, 2003)
This work offers a detailed analysis of Puritan iconoclasm in England during the 1640s. It looks at the reasons for the resurgence of image-breaking a hundred years after the break with Rome, and the extent of the phenomenon. Initially a reaction to the emphasis on ceremony and the 'beauty of holiness' under Archbishop Laud, the attack on 'innovations', such as communion rails, images and stained glass windows, developed into a major campaign driven forward by the Long Parliament as part of its religious reformation.